Penerjemahan Teks Medis Bahasa Inggris ke Bahasa Indonesia oleh Mahasiswa - Pantouw, Lidya Anita Afni; Warouw, Maya Pinkan; Marentek, Adriyani (Universitas Sam Ratulangi, 2019)
This research focuses on the problems in the use and application of techniques and the process of translating of Nursing and Midwifery students at Polytechnic of Health Manado. The objectives of the research are to describe the technique as well as to analyze the process of translating medical texts that apply within the scope of learning of these students. This study is descriptive research, of the text analysis type (content analysis), using primary data taken from students. The data of this research were collected purposively from the respondents by referring, talking and taking note techniques. The analysis process uses methods of data reduction, data presentation, and drawing conclusions or verification. After analysis, the results of the study are as follows. The most popular translation techniques used in the translation of medical texts are borrowing techniques, amplification, established equivalent, adaptations and reductions which appear to be inseparable from the influence of the level of competence and the culture of language use of the translators. The translation process that is applied is analyzed in two groups which are groups that perform ideal stages: analysis, transfer and adjustment by rearranging existing sentences, and groups that do not perform the ideal stage: analysis and adjustment. In general, this happens because of the considerations of the students regarding the purpose of translating the text itself. The stage will be carried out perfectly if there is a demand assessment, and is not perfect if it is only as a reference in making relevant tasks. Keywords: translation techniques, translation process, medical texts, effects of translation results.